2001
DOI: 10.1046/j.1468-1293.2001.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapy with saquinavir, ritonavir and stavudine in moderately to severely immunosuppressed HIV‐infected protease inhibitor‐naive patients

Abstract: In protease- and stavudine-naive HIV-infected patients with moderate to severe immunosuppression, saquinavir in combination with ritonavir and stavudine caused a substantial long-term decrease in plasma viral load in approximately half the participants and a substantial increase in CD4 cell counts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated that the combination of RTV plus SQV reduces plasma HIV‐1 viral load to a similar extent to that of a single PI‐based regimen [4–9]. These studies, however, either did not use control groups, reported only 24 weeks follow‐up data, or compared different dosing or intensification regimens of RTV plus SQV.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that the combination of RTV plus SQV reduces plasma HIV‐1 viral load to a similar extent to that of a single PI‐based regimen [4–9]. These studies, however, either did not use control groups, reported only 24 weeks follow‐up data, or compared different dosing or intensification regimens of RTV plus SQV.…”
Section: Introductionmentioning
confidence: 99%